2014
DOI: 10.1007/s10903-014-0059-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Influenza Vaccination on Acute Respiratory Symptoms in Malaysian Hajj Pilgrims

Abstract: Respiratory illness were a major problem and caused high hospital admission during hajj seasons. One of the contributing cause to this illness is infection. Various measures had been implemented to reduce respiratory infections. The aim on the study is to determine the effect of influenza vaccination against acute respiratory illness among Malaysian Hajj pilgrims. This is an observational cohort study. Influenza vaccination was given to pilgrims at least 2 weeks prior to departure. The occurrence of symptoms f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
2
8
1
Order By: Relevance
“…Coverage of seasonal influenza vaccination among pilgrims was evaluated in many studies, which have yielded varying results, with reported rates of influenza vaccination ranged from 1.1% to 100% [14,15,18,[21][22][23]25,26,28,29,[31][32][33][34]36,37,[41][42][43][44][45][46][47][48][49][50][51][53][54][55][56]. A variation over time in influenza vaccination coverage was observed, as exemplified by a rate of 10.5% observed in a survey of pilgrims from Riyadh in 2003 [43], but 94.4% in a similar survey in 2010 [32,33,36].…”
Section: Cohort Studies Addressing the Prevalence Of Respiratory Tracmentioning
confidence: 99%
“…Coverage of seasonal influenza vaccination among pilgrims was evaluated in many studies, which have yielded varying results, with reported rates of influenza vaccination ranged from 1.1% to 100% [14,15,18,[21][22][23]25,26,28,29,[31][32][33][34]36,37,[41][42][43][44][45][46][47][48][49][50][51][53][54][55][56]. A variation over time in influenza vaccination coverage was observed, as exemplified by a rate of 10.5% observed in a survey of pilgrims from Riyadh in 2003 [43], but 94.4% in a similar survey in 2010 [32,33,36].…”
Section: Cohort Studies Addressing the Prevalence Of Respiratory Tracmentioning
confidence: 99%
“…The average score was 0.95 (standard deviation [SD] = 0.9) in the intervention group and 0.88 (SD = 0.69) in the control group ( P = 0.781). [20] In another study, Emamian et al . assessed the effects of influenza vaccination on respiratory tract infections excluding the common cold.…”
Section: Resultsmentioning
confidence: 99%
“…13 Another study among Malaysian pilgrims found that influenza vaccine was effective for 50%-60% in preventing hospitalization and pneumonia; it was 80% effective in preventing death in patients older than age 60. 15 Eventual vaccination failures might be explained by a new drift of variants or inappropriate vaccine handling and storage. * Therefore examining the circulating influenza strains is recommended in * For men, the special outfit for the hajj consists of 2 pieces of white, unsown cloth.…”
Section: P U B L I C H E a L T H C H A L L E N G E S I N M A S S G A mentioning
confidence: 99%
“…addition to strict enforcement of vaccination policy. 13,15 Among other precautionary measures, the use of a face mask is considered by some pilgrims religiously prohibited while wearing ihram. Some consider using alcohol-containing products (eg, hand sanitizers) as prohibited during Hajj ritual too, although recently religious scholars have allowed the use of alcohol for medical purposes.…”
Section: P U B L I C H E a L T H C H A L L E N G E S I N M A S S G A mentioning
confidence: 99%